Octopus magnetic bead and preparation method thereof

By preparing octopus magnetic beads with rich ciliary structure and high flexibility, the problem of low separation efficiency of traditional magnetic beads is solved, the effect of efficient separation of targets is achieved, and there are broad industrial application prospects.

CN119391002APending Publication Date: 2025-02-07TECHNICAL INST OF PHYSICS & CHEMISTRY - CHINESE ACAD OF SCI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411618535.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Traditional immunomagnetic beads have low separation efficiency due to their smooth microsphere structure and single nanostructure, which is difficult to meet the needs of clinical applications.

Method used

By preparing an octopus magnetic bead, which consists of magnetic nanoparticles and polymers, has rich cilia structure and high flexibility, the morphology and surface chemical properties of the magnetic beads are controlled by the emulsion preparation method.

Benefits of technology

Octopus magnetic beads can efficiently and specifically separate multiple targets, improve the accuracy and sensitivity of disease detection, and the preparation method is simple and fast, with industrial application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391002A_ABST
    Figure CN119391002A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of immunomagnetic beads, in particular to octopus magnetic beads and a preparation method thereof. Comprising the following steps: 1, dissolving a block copolymer in an organic solvent to prepare a polymer solution with the concentration of 1-5wt%; 2, dispersing magnetic nanoparticles in the polymer solution obtained in the step 1, and carrying out ultrasonic treatment for 10-15 minutes by virtue of ultrasonic equipment, so that the magnetic nanoparticles are uniformly dispersed; 3, under the action of an emulsification mode, adding 5-15 mL of the polymer solution in the step 2 into 150-300 mL of the surfactant aqueous solution for emulsification treatment, and after emulsification, stirring until the solvent is completely volatilized to obtain a magnetic bead dispersion liquid; and 4, transferring the magnetic bead dispersion liquid into a centrifugal tube, centrifuging at a rotating speed, and cleaning with deionized water to obtain the octopus magnetic beads. The method has the advantages of being controllable in surface appearance, adjustable in chemical property, easy to prepare on a large scale, wide in industrial application prospect and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of immunomagnetic beads, and in particular to octopus magnetic beads and a preparation method thereof. Background Art

[0002] As a hot material in the separation field, immunomagnetic beads have become the gold standard for the separation of multiple disease markers. However, most traditional immunomagnetic beads are smooth microspheres that rely solely on molecular recognition to separate disease markers, and the separation efficiency is not high. A few magnetic beads have some nanostructures, but these magnetic beads have a single surface structure and poor adjustability, making it difficult to maximize the potential advantages of magnetic bead materials, hindering their development towards clinical applications.

[0003] To this end, it is urgent to develop magnetic beads with rich ciliary structures. Just like the octopus in the ocean uses long and soft tentacles to efficiently hunt, the long and flexible cilia on the magnetic beads can enhance the interaction with disease markers, thereby efficiently and specifically separating multiple targets.

[0004] Therefore, the present application proposes an octopus magnetic bead and a preparation method thereof. Summary of the invention

[0005] In order to make up for the deficiencies of the prior art and solve the technical problems existing in the background technology, the present invention proposes an octopus magnetic bead and a preparation method thereof.

[0006] The present invention is achieved through the following technical solutions: A method for preparing octopus magnetic beads comprises the following steps: Step 1: dissolving the block copolymer in an organic solvent to prepare a polymer solution with a concentration of 1-5wt%; Step 2: Disperse the magnetic nanoparticles in the polymer solution of step 1, and perform ultrasonic treatment for 10-15 minutes by ultrasonic equipment to make them evenly dispersed; Step 3: Under the action of emulsification, 5-15 mL of the polymer solution in step 2 is added to 150-300 mL of a surfactant aqueous solution for emulsification, and stirred until the solvent evaporates to obtain a magnetic bead dispersion; Step 4: Transfer the magnetic bead dispersion to a centrifuge tube, centrifuge at 6000 rpm and wash with deionized water to obtain the octopus magnetic beads.

[0007] Preferably, the block copolymer is a diblock copolymer or a triblock or higher copolymer, and the block copolymer comprises a hydrophobic segment and a hydrophilic segment; the molecular weight of the hydrophobic segment is 10kDa-200kDa, the molecular weight of the hydrophilic segment is 1kDa-100kDa, and the molecular weight ratio of the hydrophobic segment to the hydrophilic segment is 5:1-100:1.

[0008] Preferably, the hydrophobic segment comprises one of polylactic acid, polylactide, polylactic acid / glycolic acid copolymer, polystyrene, polymethyl methacrylate, polydimethylsiloxane, and polyisobutylene; The hydrophilic segment includes one of polyethylene glycol, poly-4-vinyl pyridine, polyacrylic acid, polyethylene glycol methyl ether methacrylate, and poly N,N-dimethylacrylamide.

[0009] Preferably, the mass concentration of the block copolymer in the block copolymer solution is 1 mg / mL-500 mg / mL; The magnetic nanoparticles include one or more of ferroferric oxide, ferrous oxide, cobalt oxide, and manganese-zinc-iron.

[0010] Preferably, the organic solvent includes one or more combinations of dichloromethane, chloroform, 1,2-dichloroethane, trichloroethane, carbon tetrachloride, methyl methacrylate, ethyl acetate, dimethyl carbonate, ethylene glycol dimethyl ether, dioxane, benzene, toluene, xylene, tetrahydrofuran, N,N-dimethylformamide, and acetone.

[0011] Preferably, the surfactant includes one or more combinations of sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, and polyvinyl alcohol, and the mass concentration of the surfactant in the surfactant aqueous solution is 0 mg / mL-100 mg / mL, and the surfactant aqueous solution is kept warm at 40° C. for 20 minutes.

[0012] Preferably, the emulsification method includes a homogenizer, a high-speed disperser, an ultrasonic cell disruptor, a membrane emulsifier, and a mechanical stirrer. The rotation speed of the volatile solvent after emulsification is 0rpm-10000rpm, and the centrifugal speed is 500rpm-20000rpm.

[0013] Octopus magnetic beads prepared by the above-mentioned octopus magnetic bead preparation method, the magnetic beads are composed of magnetic nanoparticles and high molecular polymers, and the morphology of the magnetic beads is octopus-shaped, and the surface of the magnetic beads has rich cilia structure, and the cilia have a high aspect ratio.

[0014] Preferably, the number of cilia with a rich ciliary structure is more than 3, and the diameter of each cilia is about 30-300 nanometers and the length is more than 1 micron; and the aspect ratio of the cilia is more than 10, with good flexibility and the ability to quickly deform.

[0015] Preferably, the magnetic beads can also be loaded with functional units, and the functional units include one or more of ferroferric oxide nanoparticles, gold nanoparticles, silver nanoparticles, graphene nanosheets, quantum dots, doxorubicin, paclitaxel, quaternary ammonium salts, and gene transfection molecules.

[0016] The beneficial effects of the present invention are: 1. The octopus magnetic beads provided by the present invention can carry a variety of functional units and are easy to be surface-modified, and can separate specific markers in a complex biological fluid environment; in addition, the long and soft cilia can detect deformation and significantly improve the interaction between the magnetic beads and disease markers, thereby efficiently separating a variety of targets to improve the accuracy and sensitivity of disease detection.

[0017] 2. The preparation method of the present invention is simple and rapid. It uses a high molecular polymer as a raw material, dissolves it in an organic solvent, and adds magnetic nanoparticles to disperse evenly as an oil phase. The oil phase is then slowly injected into the aqueous phase for emulsification. The solvent is volatilized in an aqueous environment to induce self-assembly of the block polymer to obtain octopus magnetic beads. This method has the advantages of controllable surface morphology, adjustable chemical properties, easy large-scale preparation, and broad prospects for industrial application. The prepared new octopus magnetic beads have great application prospects in chemical, biological and industrial fields such as liquid biopsy, tumor diagnosis, and drug release.

[0018] 3. The present invention is prepared by emulsion, and the physical and chemical properties of the magnetic beads are controlled by regulating polymer molecular weight, segment ratio, concentration, temperature, dispersion speed, magnetic content and other conditions, including the morphology, particle size, surface groups, number, diameter, length and flexibility of the cilia of the magnetic beads, so as to achieve adjustable morphology, particle size and surface chemical properties of the magnetic beads; the number, diameter, length and flexibility of the cilia in the magnetic beads are adjustable. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Schematic diagram of preparing octopus magnetic beads in the present invention; in, Figure 1 A is a schematic diagram of the preparation of octopus magnetic beads. Figure 1 B is the in-situ optical microscope observation of the growth process of the octopus magnetic beads; Figure 2 This is a scanning electron microscope photograph of the octopus magnetic beads prepared in Example 1 of the present invention; Figure 3 This is a morphological characteristic diagram of the octopus magnetic beads prepared in Example 1 of the present invention; in, Figure 3 A is the size statistics of the octopus magnetic bead core. Figure 3 B is a statistical graph of the cilia length of the octopus magnetic beads; Figure 4 This is a magnetic response performance diagram of the octopus magnetic beads prepared in Example 1 of the present invention; in, Figure 4 A is the TEM image of the octopus magnetic beads. Figure 4 B is the hysteresis loop diagram, Figure 4C is the magnetic adsorption performance diagram of Octopus magnetic beads; Figure 5 This is a scanning electron microscope photograph of the octopus magnetic beads prepared in Example 2 of the present invention; Figure 6 This is a scanning electron microscope photograph of the octopus magnetic beads prepared in Example 3 of the present invention; Figure 7 This is a scanning electron microscope photograph of the octopus magnetic beads prepared in Example 4 of the present invention; Figure 8 This is a scanning electron microscope photograph of the octopus magnetic beads prepared in Example 5 of the present invention; Fig. 9 This is a graph showing the cancer cell separation performance of the Octopus magnetic beads prepared in Example 1 of the present invention; in, Fig. 9 A is the separation efficiency diagram under different ratios of magnetic beads to cancer cells. Fig. 9 B is the separation efficiency diagram at different capture times. Fig. 9 C is the separation efficiency of Octopus magnetic beads for different cells. Fig. 9 D is a comparison chart of the separation efficiency of Octopus magnetic beads and commercial magnetic beads; Fig.10 This is a diagram of the interaction between the octopus magnetic beads prepared in Example 1 of the present invention and cancer cells. DETAILED DESCRIPTION

[0020] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0021] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar to or equivalent to the described content can be applied to the method of the present invention. The present invention is further described according to the accompanying drawings and specific embodiments of the present invention, and the preferred implementation methods and materials described in the present invention are only for demonstration purposes.

[0022] like Figure 1-Figure 10 As shown: Embodiment 1: a) dissolving a triblock polymer having a molecular weight ratio of hydrophobic segments to hydrophilic segments of 9:1 in dichloromethane to obtain a block polymer solution having a concentration of 3 wt %; b) dispersing the ferroferric oxide magnetic nanoparticles in the dichloromethane solution of the block copolymer and ultrasonically treating the solution for 10 minutes to make the solution uniformly dispersed; c) keeping the polyvinyl alcohol aqueous solution at 40°C for 20 minutes; d) Take 10 ml of the block polymer solution obtained in (b) and slowly inject it into the 200 ml of the polyvinyl alcohol aqueous solution in (c), and use a homogenizer at 6000 rpm and react at 40°C for 2 h; e) The magnetic beads obtained by the reaction are washed by centrifugation and then freeze-dried for storage.

[0023] The surface of the prepared octopus magnetic beads showed abundant long and soft ciliary structures through SEM characterization. The beads were uniform in size and had no obvious defects. Figure 2 shown.

[0024] Embodiment 2: a) dissolving a diblock polymer having a molecular weight ratio of hydrophobic segments to hydrophilic segments of 15:1 in dichloromethane to obtain a block polymer solution having a concentration of 3 wt %; b) dispersing the ferroferric oxide magnetic nanoparticles in the dichloromethane solution of the block copolymer and ultrasonically treating the solution for 10 minutes to make the solution uniformly dispersed; c) keeping the polyvinyl alcohol aqueous solution at 40°C for 20 minutes; d) Take 10 ml of the block polymer solution obtained in (b) and slowly inject it into the 200 ml of the polyvinyl alcohol aqueous solution in (c), and use a homogenizer at 6000 rpm and react at 40°C for 2 h; e) The magnetic beads obtained by the reaction are washed by centrifugation and then freeze-dried for storage.

[0025] The surface of the prepared magnetic beads showed abundant long and soft burr structures through SEM characterization. The beads were uniform in size and had no obvious defects. Figure 5 shown.

[0026] Embodiment 3: a) dissolving a triblock polymer having a molecular weight ratio of hydrophobic segments to hydrophilic segments of 15:1 in dichloromethane and methyl methacrylate in a volume ratio of 19:1 to obtain a block polymer solution having a concentration of 3 wt%; b) dispersing the ferroferric oxide magnetic nanoparticles in the dichloromethane solution of the block copolymer and ultrasonically treating the solution for 10 minutes to make the solution uniformly dispersed; c) keeping the polyvinyl alcohol aqueous solution at 40°C for 20 minutes; d) Take 10 ml of the block polymer solution obtained in (b) and slowly inject it into the 200 ml of the polyvinyl alcohol aqueous solution in (c), and use a homogenizer at 6000 rpm and react at 40°C for 2 h; e) The magnetic beads obtained by the reaction are washed by centrifugation and then freeze-dried for storage.

[0027] The surface of the prepared octopus magnetic beads showed abundant long and soft burr structures through SEM characterization. The beads were uniform in size and had no obvious defects. Figure 6 shown.

[0028] Embodiment 4: a) dissolving a triblock polymer having a molecular weight ratio of hydrophobic segment to hydrophilic segment of 9:1 and a triblock polymer having a molecular weight ratio of hydrophobic segment to hydrophilic segment of 13.5:1 in dichloromethane at a volume ratio of 1:1 to obtain a block polymer solution having a concentration of 3 wt%; b) dispersing the ferroferric oxide magnetic nanoparticles in the dichloromethane solution of the block copolymer and ultrasonically treating the solution for 10 minutes to make the solution uniformly dispersed; c) keeping the polyvinyl alcohol aqueous solution at 40°C for 20 minutes; d) Take 10 ml of the block polymer solution obtained in (b) and slowly inject it into the 200 ml of the polyvinyl alcohol aqueous solution in (c), and use a homogenizer at 6000 rpm and react at 40°C for 2 h; e) The magnetic beads obtained by the reaction are washed by centrifugation and then freeze-dried for storage.

[0029] The surface of the prepared octopus magnetic beads showed abundant long and soft burr structures through SEM characterization. The beads were uniform in size and had no obvious defects. Figure 7 shown.

[0030] Embodiment 5: a) dissolving a triblock polymer having a molecular weight ratio of hydrophobic segments to hydrophilic segments of 9:1 and polystyrene in a volume ratio of 1:5 in dichloromethane to obtain a block polymer solution having a concentration of 3 wt %; b) dispersing the ferroferric oxide magnetic nanoparticles in the dichloromethane solution of the block copolymer and ultrasonically treating the solution for 10 minutes to make the solution uniformly dispersed; c) keeping the polyvinyl alcohol aqueous solution at 40°C for 20 minutes; d) Take 10 ml of the block polymer solution obtained in (b) and slowly inject it into the 200 ml of the polyvinyl alcohol aqueous solution in (c), and use a homogenizer at 6000 rpm and react at 40°C for 2 h; e) The magnetic beads obtained by the reaction are washed by centrifugation and then freeze-dried for storage.

[0031] The surface of the prepared octopus magnetic beads showed abundant long and soft burr structures through SEM characterization. The beads were uniform in size and had no obvious defects. Figure 8 shown.

[0032] Embodiment 6: a) The octopus magnetic beads obtained in Example 1 were modified with specific antibodies, and 10 7 Add 10 magnetic beads to 5 The prostate cancer cells were captured at 37°C for 10, 20, 30, 45, and 60 minutes. After the capture, they were washed three times with PBS and the capture efficiency was calculated to obtain the cancer cell separation efficiency at different capture times. b) The octopus magnetic beads obtained in Example 1 were modified with specific antibodies, and 5*10 5 , 10 6 , 5*10 6 , 10 7 , 2*10 7 Add 10 magnetic beads to 5 The prostate cancer cells were captured at 37°C for 30 minutes, and washed three times with PBS after the capture. The capture efficiency was calculated to obtain the separation efficiency at different ratios of magnetic beads to cancer cells. c) The octopus magnetic beads obtained in Example 1 were modified with specific antibodies, and 10 7 Add 10 magnetic beads to 5 Different cells, mainly prostate cancer cells, breast cancer cells, hepatocellular carcinoma cells, lymphoma cells and T cells, were captured at 37°C for 30 minutes. After the capture, they were washed three times with PBS, and the capture efficiency was calculated to obtain the separation efficiency of Octopus magnetic beads and different cells. d) The octopus magnetic beads and commercial magnetic beads obtained in Example 1 were modified with specific antibodies, and 10 7 Different magnetic beads were added to 10 5 The prostate cancer cells were captured at 37°C for 30 minutes, and washed three times with PBS after the capture, and the capture efficiency was calculated; According to statistics, the prepared octopus magnetic beads have a higher capture efficiency than commercial magnetic beads and can efficiently and specifically separate cancer cells within 30 minutes. The results are shown in the attached Fig. 9 shown.

[0033] in, Fig. 9 A is a graph showing the separation efficiency at different ratios of magnetic beads to cancer cells. When the ratio of octopus magnetic beads to cancer cells is 100:1, the capture efficiency can exceed 90%.

[0034] Fig. 9 B is the separation efficiency diagram under different capture times. Octopus magnetic beads can achieve a high capture efficiency of over 90% in about 30 minutes.

[0035] Fig. 9C is the separation efficiency diagram of Octopus magnetic beads for different cells. It can be seen that Octopus magnetic beads can efficiently separate cancer cells, but have a lower separation efficiency for non-specific lymphocytes, which reflects that our Octopus magnetic beads exhibit high separation specificity.

[0036] Fig. 9 D is a comparison chart of the separation efficiency of Octopus magnetic beads and commercial magnetic beads. It can be seen that compared with commercial magnetic beads, Octopus magnetic beads have significantly improved cancer cell separation efficiency.

[0037] Embodiment 7: An octopus magnetic bead is composed of magnetic nanoparticles and high molecular polymers, and the morphology of the magnetic bead is octopus-shaped. The surface of the magnetic bead has rich cilia structure, and the cilia have a high aspect ratio.

[0038] The number of cilia with rich ciliary structure is more than 3, and the diameter of each cilia is about 30-300 nanometers and the length is more than 1 micron; the aspect ratio of the cilia is more than 10, with good flexibility and the ability to deform quickly.

[0039] like Figure 3 As shown, it can be seen that the octopus magnetic beads prepared by the preparation method of the present application have a rich ciliary structure, and the length of the cilia is about twice that of the nucleus. The long and soft ciliary structure is conducive to actively generating deformation and entanglement with disease markers such as cells, thereby improving the separation efficiency.

[0040] like Figure 4 As shown, it can be seen that the octopus magnetic beads have excellent magnetic response performance, because magnetic response performance is also one of the important properties in separating disease markers.

[0041] in, Figure 4 A is the TEM image of the octopus magnetic beads, which shows that the iron oxide magnetic nanoparticles are successfully encapsulated in the octopus magnetic beads. The nanoparticles are evenly distributed in the core and cilia.

[0042] Figure 4 B is a hysteresis loop diagram, which shows that the prepared octopus magnetic beads have good magnetic strength.

[0043] Figure 4 C is the magnetic adsorption performance diagram of Octopus magnetic beads. Octopus magnetic beads are evenly dispersed in the aqueous solution. After adding the magnet, they can be completely separated by magnetic adsorption in about 56 seconds, showing excellent magnetic response performance.

[0044] like Figure 1As shown in the figure, the polymer oil phase is added to the water phase for emulsification to form an oil-in-water emulsion. As the organic solvent evaporates, the emulsion droplets continue to shrink. When they shrink to a certain critical value, under the action of the block copolymer, the emulsion droplets no longer maintain a spherical shape, and wrinkles begin to form on the interface, causing deformation. The organic solvent further evaporates, causing the deformed part of the emulsion droplets to continue to grow outward and become longer. Finally, when the organic solvent evaporates, the block copolymer will precipitate and solidify in the solution to form a ciliary structure.

[0045] in, Figure 1 A is a schematic diagram of the preparation of octopus magnetic beads. As the solvent evaporates, the emulsion droplets gradually shrink. After shrinking to a critical volume, the emulsion droplets no longer maintain a spherical shape, but undergo a shape change to produce cilia. The cilia then continue to elongate and solidify to form octopus magnetic beads.

[0046] Figure 1 B is an optical microscope in-situ observation of the growth process of the octopus magnetic beads. Corresponding to the schematic diagram, the emulsion droplets gradually shrink, deform and begin to grow cilia. Then the cilia continue to elongate and solidify to form octopus magnetic beads with rich ciliary structures.

[0047] In addition, the reason for the formation of the cilia structure is the same as above. The polymer used is a kind of soft material with good flexibility. The cilia structure produced has a large aspect ratio. The length of the cilia is much larger than the diameter of the nucleus (see the structural diagram of the embodiment). The thin, long and flexible characteristics of the cilia make this octopus magnetic bead very easy to deform in the solution. After contacting with the disease marker, it can be deformed to actively contact and entangle the marker, thereby improving the separation efficiency. Fig.10 As shown, the octopus magnetic beads can actively deform and fit closely with cancer cells, and the cilia wrap around the cells, which enhances the interaction between the octopus magnetic beads and cancer cells, thereby improving the efficiency of cancer cell separation.

[0048] Embodiment 8: The magnetic beads can also load functional units, and the functional units include one or more of ferroferric oxide nanoparticles, gold nanoparticles, silver nanoparticles, graphene nanosheets, quantum dots, doxorubicin, paclitaxel, quaternary ammonium salts, and gene transfection molecules.

[0049] Adding functional units to magnetic beads can give them multiple functions. For example, adding quantum dots can be used for bioimaging, adding gold nanoparticles can be used for photothermal therapy of diseases, and adding doxorubicin, paclitaxel, etc. can be used for tumor treatment. The adding method is to disperse these functional units in the oil phase when preparing the polymer solution, and form an oil-in-water emulsion after emulsification. When cilia are formed, they will be assembled together with the block copolymer to encapsulate these functional units in the octopus magnetic beads.

[0050] Any matters not described in the present invention are applicable to the prior art.

Claims

1. A method for preparing octopus magnetic beads, characterized in that: The following steps are involved: Step 1: dissolving the block copolymer in an organic solvent to prepare a polymer solution with a concentration of 1-5wt%; Step 2: Disperse the magnetic nanoparticles in the polymer solution of step 1, and perform ultrasonic treatment for 10-15 minutes to make them evenly dispersed; Step 3: Under the action of emulsification, 5-15 mL of the polymer solution in step 2 is added to 150-300 mL of a surfactant aqueous solution for emulsification, and stirred until the solvent evaporates to obtain a magnetic bead dispersion; Step 4: Transfer the magnetic bead dispersion to a centrifuge tube, centrifuge at 6000 rpm and wash with deionized water to obtain the octopus magnetic beads.

2. The method for preparing octopus magnetic beads according to claim 1, characterized in that: The block copolymer is a diblock copolymer or a triblock or higher copolymer, and the block copolymer includes a hydrophobic segment and a hydrophilic segment; the molecular weight of the hydrophobic segment is 10kDa-200kDa, the molecular weight of the hydrophilic segment is 1kDa-100kDa, and the molecular weight ratio of the hydrophobic segment to the hydrophilic segment is 5:1-100:

1.

3. The method for preparing octopus magnetic beads according to claim 2, characterized in that: The hydrophobic segment comprises one of polylactic acid, polylactide, polylactic acid / glycolic acid copolymer, polystyrene, polymethyl methacrylate, polydimethylsiloxane, and polyisobutylene; The hydrophilic segment includes one of polyethylene glycol, poly-4-vinyl pyridine, polyacrylic acid, polyethylene glycol methyl ether methacrylate, and poly N,N-dimethylacrylamide.

4. The method for preparing octopus magnetic beads according to claim 1, characterized in that: The mass concentration of the block copolymer in the block copolymer solution is 1 mg / mL-500 mg / mL; The magnetic nanoparticles include one or more of ferroferric oxide, ferrous oxide, cobalt oxide, and manganese-zinc-iron.

5. The method for preparing octopus magnetic beads according to claim 1, characterized in that: The organic solvent includes one or more combinations of dichloromethane, chloroform, 1,2-dichloroethane, trichloroethane, carbon tetrachloride, methyl methacrylate, ethyl acetate, dimethyl carbonate, ethylene glycol dimethyl ether, dioxane, benzene, toluene, xylene, tetrahydrofuran, N,N-dimethylformamide, and acetone.

6. The method for preparing octopus magnetic beads according to claim 1, characterized in that: The surfactant includes one or more combinations of sodium dodecyl sulfate, hexadecyltrimethylammonium bromide, and polyvinyl alcohol, and the mass concentration of the surfactant in the surfactant aqueous solution is 0 mg / mL-100 mg / mL, and the surfactant aqueous solution is kept warm at 40° C. for 20 minutes.

7. The method for preparing octopus magnetic beads according to claim 1, characterized in that: The emulsification method includes a homogenizer, a high-speed disperser, an ultrasonic cell disruptor, a membrane emulsifier, and a mechanical stirrer. The rotation speed of the volatile solvent after emulsification is 0rpm-10000rpm, and the centrifugal rotation speed is 500rpm-20000rpm.

8. An octopus magnetic bead prepared by the method for preparing octopus magnetic beads according to any one of claims 1 to 7, characterized in that: The magnetic beads are composed of magnetic nanoparticles and high molecular polymers, and the morphology of the magnetic beads is octopus-shaped. The surface of the magnetic beads has abundant cilia structures, and the cilia have a high aspect ratio.

9. An octopus magnetic bead according to claim 8, characterized in that: The number of cilia with rich ciliary structure is more than 3, and the diameter of each cilia is about 30-300 nanometers and the length is more than 1 micron; the aspect ratio of the cilia is more than 10, with good flexibility and the ability to deform quickly.

10. The octopus magnetic bead according to claim 8, characterized in that: The magnetic beads can also load functional units, and the functional units include one or more of ferroferric oxide nanoparticles, gold nanoparticles, silver nanoparticles, graphene nanosheets, quantum dots, doxorubicin, paclitaxel, quaternary ammonium salts, and gene transfection molecules.

Citation Information

Patent Citations

  • Polylactic acid-polyethylene glycol block copolymer-based magnetic microsphere preparation method

    CN103980506A

  • Micro-nano magnetic polymer microsphere with surface topological structure and preparation method of micro-nano magnetic polymer microsphere

    CN114249909A

  • Polymer magnetic bead with bionic micro-nano fractal structure as well as preparation method and application of polymer magnetic bead

    CN115677935A